2020
DOI: 10.1177/1535370220963793
|View full text |Cite
|
Sign up to set email alerts
|

Detection of severe acute respiratory syndrome coronavirus 2 and influenza viruses based on CRISPR-Cas12a

Abstract: Due to the common symptoms of COVID-19, patients are similar to influenza-like illness. Therefore, the detection method would be crucial to discriminate between SARS-CoV-2 and influenza virus-infected patients. In this study, CRISPR-Cas12a-based detection was applied for detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza A virus, and influenza B virus which would be a practical and attractive application for screening of patients with COVID-19 and influenza in areas with limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
88
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 13 publications
2
88
0
Order By: Relevance
“…According to our study ( Table 2 & Supplementary Table 1), the CRISPR-Cas12a assays based on N1 ( Ding et al, 2020 ) and S ( Mayuramart et al, 2020 ) genes yielded diagnostic accuracy (≥ 95%) comparable to the qRT-PCR results). The CRISPR-Cas12a assays within E, N2 ( Broughton et al, 2020 ) and S ( Mayuramart et al, 2020 ) genes provided suitable sensitivity of detection (≥ 95%) while N1 ( Ding et al, 2020 ) and S ( Mayuramart et al, 2020 ) genes provided excellent specificity of detection (100%). Ideally, multiple target genes should be detected by using CRISPR-Cas12a to ensure the most effective SARS-CoV-2 detection.…”
supporting
confidence: 52%
See 4 more Smart Citations
“…According to our study ( Table 2 & Supplementary Table 1), the CRISPR-Cas12a assays based on N1 ( Ding et al, 2020 ) and S ( Mayuramart et al, 2020 ) genes yielded diagnostic accuracy (≥ 95%) comparable to the qRT-PCR results). The CRISPR-Cas12a assays within E, N2 ( Broughton et al, 2020 ) and S ( Mayuramart et al, 2020 ) genes provided suitable sensitivity of detection (≥ 95%) while N1 ( Ding et al, 2020 ) and S ( Mayuramart et al, 2020 ) genes provided excellent specificity of detection (100%). Ideally, multiple target genes should be detected by using CRISPR-Cas12a to ensure the most effective SARS-CoV-2 detection.…”
supporting
confidence: 52%
“…The results revealed that detection of the E gene ( Broughton et al, 2020 ) of SARS-CoV-2 based on CRISPR-Cas12a provides the highest sensitivity (97.7%). On the other hand, S ( Mayuramart et al, 2020 ) and N1 ( Ding et al, 2020 ) genes yielded the highest specificity (100%). Interestingly, S ( Mayuramart et al, 2020 ) and N1 ( Ding et al, 2020 ) genes represented acceptable diagnostic accuracy as high as 98.1% and 97.2%, respectively ( Table 2 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations